Freedom Institute, Neoliberalism and Phenomenon of Intellectual Trade - Herdi Sahrasad (Budapest International Research and Critics University, 2017)
This article highlights the phenomenon of the Freedom Institute, an NGO in which one of the main actors, Rizal Mallarangeng, who acts as if